Comprehensive Survey on Load Balancing Techniques in Cloud Computing Environments (International Journal of Scientific Research in Science and Technology, 2024)
The notion of load balancing is necessary to maximise the use of cloud resources due to the daily increase in internet traffic. For the system's performance and stability, load balancing becomes essential. Consequently, an algorithmic strategy is needed to balance work among virtual machines (VMs) and improve system performance. Techniques: To provide load balancing and QoS, task scheduling methods are employed. Cloud computing is an entirely internet-based method in which all information and programs are stored on a cloud, which is made up of thousands of machines connected in a complex way. By guaranteeing optimal use of available resources, a load balancing algorithmic strategy seeks to improve the response time of user-submitted applications. The primary goal of load balancing techniques is to accelerate the execution of programs on resources whose workload fluctuates in unanticipated ways during runtime.
Keywords: Cloud load balancing; Round robin algorithm; Load Balancing; Makespan Response Time; Task Scheduling